Corneal collagen crosslinking with riboflavin and ultraviolet-A light in progressive keratoconus: ten-year results - Raiskup, Frederik; Theuring, Anja; Pillunat, Lutz E; Spoerl, Eberhard (Journal of cataract and refractive surgery, 2015)
PURPOSE: To analyze the 10-year results of corneal collagen crosslinking (CXL) for keratoconus. SETTING: Department of Ophthalmology, University Hospital, Dresden, Germany. DESIGN: Retrospective interventional case series. METHODS: The study included eyes treated for progressive keratoconus from 2000 to 2004. Corneal collagen crosslinking was performed by applying riboflavin and ultraviolet-A. The corrected distance visual acuity (CDVA), corneal topography, and endothelial cell count (ECC) were recorded preoperatively and 10 years postoperatively. RESULTS: The study enrolled 24 patients (34 eyes). The mean age of the 18 men and 6 women was 28.4 years ± 7.3 (SD) and the mean follow-up, 131.9 ± 20.1 months. The mean apical keratometry (K) value was 61.5 diopters (D) preoperatively and 55.3 D 10 years postoperatively; the decrease was statistically significant (P<.001). The mean values for maximum K (53.2 D and 49.56 D, respectively) and minimum K (47.5 D and 45.5 D, respectively) were also significantly lower (P<.001). The preoperative and postoperative CDVA were statistically significantly different (P=.002). The mean CDVA improved by 0.14 logMAR over preoperatively; the change was statistically significant (P=.002). The ECC was unchanged. CONCLUSIONS: Corneal CXL was effective in treating progressive keratoconus, achieving long-term stabilization of the condition. It was easy to perform, had a good safety profile, and reduced the need for corneal transplantation. FINANCIAL DISCLOSURE: No author has a financial or proprietary interest in any material or method mentioned.
Keywords: dospělí; Female; Adult; mladý dospělý; ženské pohlaví; Collagen; Adolescent; Keratoconus; lidé; kolagen; Photochemotherapy; riboflavin; Ultraviolet Rays; Photosensitizing Agents; Cross-Linking Reagents; následné studie; fotosenzibilizující látky; reagencia zkříženě vázaná; retrospektivní studie; Follow-Up Studies; Male; progrese nemoci; Disease Progression; Young Adult; stroma rohovky; mužské pohlaví; zraková ostrost; Visual Acuity; fotochemoterapie; Retrospective Studies; keratokonus; mladiství; Riboflavin; Corneal Stroma; ultrafialové záření; Humans